2011
DOI: 10.2478/s11535-011-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proteasome pool in human papillary thyroid carcinoma development

Abstract: Searching the antitumor drug targets among proteasomes, “ubiquitous” enzyme systems, may provide a new impulse to the antitumor drug discovery. In this study, changes in the proteasome pool in the development of human papillary thyroid carcinoma were determined. Proteasome activities were evaluated by hydrolysis of commercial fluorogenic peptides. Changes in the expression of the total proteasome pool, proteasome 19S activator and proteolytic constitutive subunits X(β5), Y(β1) and immune subunits LMP7 (β5i) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…It was in tumor cells (not stroma cells) that the main amounts of subunit LMP2 and activator PA700 were fixed by method of immunohistochemistry. Relationships like these were earlier detected for thyroid cancer [32] . Perhaps, immune subunit LMP2 performs anti-stress functions in cells of these tumors and promotes their survival.…”
Section: Discussionsupporting
confidence: 67%
“…It was in tumor cells (not stroma cells) that the main amounts of subunit LMP2 and activator PA700 were fixed by method of immunohistochemistry. Relationships like these were earlier detected for thyroid cancer [32] . Perhaps, immune subunit LMP2 performs anti-stress functions in cells of these tumors and promotes their survival.…”
Section: Discussionsupporting
confidence: 67%
“…Since the UPS is composed of a series of highly regulated proteins, there is ample opportunity to discover new targets for cancer therapy. Indeed, the expression of many different proteasome subunits are reported to be altered in multiple different cancers, including human papillary thyroid carcinoma [ 18 ], breast cancer [ 19 , 20 , 21 , 22 , 23 ], colon cancer [ 24 , 25 ], and ovarian cancer [ 26 ], among others [ 27 , 28 , 29 , 30 ]. We recently demonstrated that two members of the 19S regulatory complex, 26S proteasome non-ATPase subunits 1 (PSMD1) and 3 (PSMD3), may be potential targets for therapy in tyrosine kinase inhibitor (TKI)-resistant chronic myeloid leukemia (CML) cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is intriguing that in other tumor types (patient thyroid papillary carcinoma, mouse hepatocellular carcinoma and mammary gland cancer) as well as in patient rectal cancer the increase in LMP2 subunit expression is much more significant in comparison with the expression of LMP7 subunit [ 2 , 21 , 22 ]. It indicates the universal role of the proteasomes with LMP2 subunit in the tumor development.…”
Section: Resultsmentioning
confidence: 99%
“…Solving this issue is tightly related to the detection of intestine areas where there are no changes in the molecule functioning that are intrinsic for tumor. In this regard, we paid attention to proteasomes, the main actors in protein hydrolysis, which largely determine the tumor fate [ 1 , 2 , 3 , 4 ]. Proteasomes control cellular proteome and regulate different processes by protein degradation and production of biologically active polypeptides and peptides.…”
Section: Introductionmentioning
confidence: 99%